Treasure in trash: A Case Study of Pet Plastic Recycling - Samani, Shamim (Common Ground Publishing Pty Ltd, 2008)
As many developing countries like Kenya become more consumerist societies, the consumption of plastics increases at an alarming rate. Though per capita consumption is low in comparison with industrialized countries, plastic application in low-cycle products pose environmental problems in countries where solid waste goes mostly to landfill. Plastic waste accounts for about 12% of total solid waste in the form of various products and packaging, and as mostly a non-biodegradable product is a long-term pollution liability. To limit the amount of material in the “waste stream”, a sustainable solution is recycling. This paper focused on a practical case study examines the sustainability elements of a private sector venture to recycle PET (a plastic used in the manufacture of beverage bottles) in Mombasa, Kenya.